PENGARUH“CUES” DALAM KEPUTUSAN PEMBELIAN SMARTPHONE (STUDI PADA MAHASISWA STIE MALANGKUÇEÇWARA MALANG) - ', Setiyawan (Arthavidya Jurnal Ilmiah Ekonomi, 2015)
Consumers always use quality cues to predict attributes they want touse in product (Smartphone). This study used indirect extrinsic cues (X1) topurchase decision (Y) through quality perception (Z) pathway track model. Thefirst pathway is direct influence of extrinsic cues (X1) and intrinsic cues (X2) toquality perception. The second pathway from track analysis model is directinfluence and indirect extrinsic cues (X1) and intrinsic cues (X2) throughpurchase decision (Y).This study result shows that intrinsic cues variable did notaffect the decision of buying Smartphone through quality perception. It meansthat consumer sometimes can not evaluate cues accurately related to qualityassessment in post-purchasing evaluation due to misinterpret or limitation ofaccessing product information. Extrinsic cues positively affect purchasingdecision in buying Smartphone through quality perception due to increasing thequality perception in consumer assessment about overall product eminence willhave big impact in interest extrinsic of consumers who will buy Smartphoneproduct. Consumers perception about purchasing quality is based on qualitycues.Keywords: Extrinsic Cues, Intrinsic Cues, Purchase decision